A Pilot Investigation of the Graduated Recovery Intervention Program (GRIP) for First Episode Psychosis - Penn, David L. (2011)
The Graduated Recovery Intervention Program (GRIP) is a new individual cognitive-behavioral therapy program designed to facilitate functional recovery in people who have experienced an initial episode of psychosis. The purpose of this study was to evaluate the feasibility and tolerability of the GRIP intervention, and to compare the effectiveness of GRIP versus treatment as usual (TAU) for improving specific clinical and psychosocial outcomes. Forty-six individuals with first episode psychosis were randomized to GRIP + TAU or TAU alone. Primary outcomes focused on social and role functioning, and quality of life. Secondary outcomes included psychotic symptoms, depression, substance use, social support, attitudes toward medications, well-being, and hospitalizations. The results indicate that GRIP was well-tolerated, as evidenced by good attendance and low drop-out rates, and well-received (based on positive feedback from participants). Although the majority of mixed-model analyses were not statistically significant, examination of within-group changes and effect sizes suggest an advantage for GRIP over TAU in improving functional outcomes. These advantages and the fact that the GRIP intervention demonstrated feasibility and tolerability suggest that this intervention is worthy of further investigation.